Assessing the cognitive salience of wild fauna in the Barranca de Metztitlán Biosphere Reserve, Mexico - Zepeda Hernández, Zeltzin Ketzalken; Pulido Silva, María Teresa; Sánchez Rojas, Gerardo (Ethnobiology and Conservation, 2024)
It is important to document the knowledge possessed by rural people about the species of flora and fauna in their environment, so that this knowledge can be incorporated into conservation efforts. We set out to learn about the traditional knowledge held by the inhabitants of the Barranca de Metztitlán Biosphere Reserve (BMBR) regarding the fauna in their environment, identifying which wild species they recognize and what cognitive salience they assign to them. We also compared knowledge between people who live in the valley (La Vega) and the mountains (La Sierra), and between men and women to determine whether knowledge was different. We conducted semi-structured interviews from April 2016 to February 2017. In order to evaluate traditional knowledge, we used the Smith index because it combines the frequency and order of mention of the listed elements. We found that in the BMBR local people recognized 37 wild species, including 25 mammals, 9 birds, two reptiles and one unidentified species. The Smith Index is only correlated with mention frequency, but not with mention order. The ethnozoological knowledge is structured by gender; while men mention 100% species of the list generated by the interviews, women only cover 59.5%. Some wild animals recorded a significant variation in the cognitive salience between La Vega and La Sierra. The local population has extensive knowledge about which wild species inhabit the area, mainly of mammals and secondarily of birds and reptiles. This knowledge should be integrated into conservation plans for the reserve.